DIGITAL MARKETING IN THE SUPERMARKET SECTOR: EVIDENCE FROM TANGARÁ DA SERRA - MT (REMUNOM, 2025)
With the advancement of technology and widespread digital connectivity, traditional marketing has given way to more dynamic and interactive strategies. This study aimed to identify and analyze the types of digital marketing used by a supermarket in Tangará da Serra/MT, assessing their relevance in the local context. The research, of an exploratory nature, involved 230 customers and an analysis of the company's social networks. The results reveal that Instagram and WhatsApp are the most effective channels for communicating with the public, directly influencing purchasing behavior. Strategies such as influencer marketing, mobile marketing and marketing on social networks stand out, demonstrating a consistent alignment between digital actions and the supermarket's commercial objectives.